Content and retention of provitamin A carotenoids following ripening and local processing of four popular Musa cultivars from Eastern Democratic Republic of Congo - Ekesa, B.N.; Kimiywe, J.; Bergh, Inge van den; Blomme, Guy; Dhuique-Mayer, Claudie; Davey, M. (Canadian Center of Science and Education, 2013)
Changes in the concentrations and retention levels of total and individual provitamin A carotenoids (pVACs) during ripening and local processing of the four most popular Musa cultivars of Eastern Democratic Republic of Congo were established through HPLC analysis. The predominant pVACs were all trans β- and α-carotene, together constituting about 90% of total pVACs content in raw and processed Musa fruit pulp. The proportion of β- and α-carotene was not significantly different in the tested East African Highland Bananas (AAA-EAHB) (‘Nshikazi’ and ‘Vulambya’); in the plantains (‘Musilongo’ and ‘Musheba’), proportion of β-carotene was almost twice that of α-carotene. An increase in total pVACs was observed during ripening, with highest levels at ripening stage 3 in all four cultivars. Total pVACs values were as high as 1081μg/100gfw in ‘Vulambya’ and 1819μg/100gfw in ‘Musilongo’. Boiling of the AAA-EAHB and AAB-Plantains resulted to retention of between 40-90% and >95% respectively. Plantains deep-fried in fully-refined palm oil and crude red palm oil for 2 minutes did not seem to lose any pVACs, the levels of total pVACs observed after frying were 100% of what was observed when the fruit was raw. Retinol Activity Equivalents (RAE), in boiled products varied between 22.3 and 173 RAEμg/100gfw, whereas deep fried products had >190 RAEμg/100g edible portion. These results show that the tested AAA-EAHBs and the plantains could meet at least 14% and 30 % of Vitamin A recommended dietary intakes respectively. The findings can therefore guide consumer consumption patterns to maximize vitamin A intake for improved health in these regions and also direct researchers in the selection of Musa cultivars to be incorporated within existing farming systems in the fight against vitamin A deficiency (VAD).